Hubungan Beban Kerja dengan Kelelahan Kerja pada Pekerja Industri Rumah Tangga Rambak Kering Desa Doplang Kecamatan Teras Boyolali - Safitri, Mudah, Sri Darnoto, SKM., M.PH (2017)
The work load is one of the factor that can make the fatigue of work. The workers will get work fatigue depends on the work load that they got before. The aim of the research is to know the relation of the work load and the work fatigue of the workers of rambak kering home industry at Doplang, Teras, boyolali. The method of the research uses analitical observasional plan with crossectional approach. The population of the research is the workers of home industry in 47 units of home industry. There are 202 people. The technique of sampling uses proporsional random sampling. The sampling of the research are 67 people. The result of the work load of the workers are 77,9% as low work load and 22,1% are as middle work load. Whereas, the distribution of the frequency of work fatigue is 79,4% included low work fatigue, then 16,2% included middle work fatigue and 4,4% included high work load. The statistical test uses Rank Spearman Rho Correlation. It is know the valve of sig p = 0,018 (p = < 0,05) and the valve of r = 0,285. It means that Ha is accepted, so there is relation. From the result of the research can be concluded that there is relation of the work load with the work fatigue of the workers of rambak kering home industry at Doplang, Teras, Boyolali.